2021
DOI: 10.3390/agronomy11010099
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis of Combined Stress Tolerance to Low Phosphorus and Drought in a Diverse Set of Mungbean Germplasm

Abstract: To understand the physiological basis of tolerance to combined stresses to low phosphorus (P) and drought in mungbean (Vignaradiata (L.) R. Wilczek), a diverse set of 100 accessions were evaluated in hydroponics at sufficient (250 μM) and low (3 μM) P and exposed to drought (dehydration) stress. The principal component analysis and ranking of accessions based on relative values revealed that IC280489, EC397142, IC76415, IC333090, IC507340, and IC121316 performed superior while IC119005, IC73401, IC488526, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…PEPC and MDH are key enzymes in the TCA cycle; the metabolites of this pathway (citrate, malate, oxalate) are exuded into the rhizosphere under low P stress. We observed enhanced exudation of organic acids in IC333090, which corroborates with the expression pattern of genes regulating their synthesis (Meena et al 2021). Similar enhancements in the transcript level of PEPCase have been reported for white lupin (Uhde-Stone et al 2003) and soybean under low P stress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…PEPC and MDH are key enzymes in the TCA cycle; the metabolites of this pathway (citrate, malate, oxalate) are exuded into the rhizosphere under low P stress. We observed enhanced exudation of organic acids in IC333090, which corroborates with the expression pattern of genes regulating their synthesis (Meena et al 2021). Similar enhancements in the transcript level of PEPCase have been reported for white lupin (Uhde-Stone et al 2003) and soybean under low P stress.…”
Section: Discussionsupporting
confidence: 89%
“…This grouping was done based on extensive physiological studies where the accessions showed tolerance to individual stresses of drought, low P as well as to their combined stress (Meena et al 2021).…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and survival of plants are normally associated with their ability to intercept light efficiently [ 28 ] and the amount of nutrients and moisture available in soil [ 29 , 30 ]. One significant finding of this study was that shading improved the height growth of H. moellendorffii in both unfertilized and fertilized plots and aboveground production in unfertilized ones.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the cytosolic P i concentration controls the rate of photosynthesis and partitioning of photoassimilates between starch and sucrose (Rychter and Rao, 2005). While the scientific literature is rich when considering how low P supply affects plants (Partelli et al, 2009;Meena et al, 2021), little is known about how extra P supply may benefit plants under stressful conditions. Under nonlimiting conditions, coffee plants receiving extra P supply (twice the recommended) presented enhanced plant hydraulic conductance, leaf carbohydrate, and chlorophyll contents, resulting in improved growth as compared with trees supplied with the recommended P fertilization (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%